Keputusan Pembelian Dipengaruhi oleh Kesadaran, Kualitas, Asosiasi dan Loyalitas Merek Melalui Kepercayaan Merek Kamera Sony Pada Komunitas Fotografi di Malang - Ramadhan, Tri Sugiarti; Farida, Eka (Fakultas Ekonomi, UIN Maliki Malang, 2020)
The purpose of this study was to determine and analyze purchasing decisions that are influenced by brand awareness, quality, association, and loyalty through brand trust. This type of research is a causal relationship with an explanatory character. The population in this research is the photography community DSLR (Digital Single Lens Reflex) camera users in Malang, East Java, totaling 190 respondents. The sampling technique used in this study was purposive sampling technique with a total sample of 66 respondents. The analysis used is path analysis, and the results show that purchasing decisions are influenced by brand awareness, quality, association, and loyalty through brand trust. The results showed that purchasing decisions are influenced by awareness, quality, association, and brand loyalty through brand trust.